1995
DOI: 10.1172/jci117968
|View full text |Cite
|
Sign up to set email alerts
|

Low-efficiency of percutaneous adenovirus-mediated arterial gene transfer in the atherosclerotic rabbit.

Abstract: Recombinant adenoviruses are the most efficient vectors with which to perform arterial gene transfer. Previous in vivo studies of adenovirus-mediated arterial transfection, however, have been performed using normal or endothelium-denuded arteries. It is unclear whether these results can be extended to atherosclerotic arteries. Accordingly, this study was designed to (a) assess the feasibility of adenovirusmediated gene transfer to atherosclerotic lesions, and (b) compare the transfection efficiency, anatomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 45 publications
6
57
2
Order By: Relevance
“…2 In order to develop a therapy to enhance collateral development, these growth factors have been tested in vivo with several delivery techniques. [4][5][6][7] Direct administration of growth factor protein was initially investigated in animal models of ischemia, which showed significant development of collateral vessels and improvement of the ischemic state. 4,5,8 However, high-dose bolus delivery has a high potential risk of systemic toxicity through cytokine diffusion into the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 In order to develop a therapy to enhance collateral development, these growth factors have been tested in vivo with several delivery techniques. [4][5][6][7] Direct administration of growth factor protein was initially investigated in animal models of ischemia, which showed significant development of collateral vessels and improvement of the ischemic state. 4,5,8 However, high-dose bolus delivery has a high potential risk of systemic toxicity through cytokine diffusion into the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
“…transferred into arterial wall cells, 6 or muscle cells 7 of ischemic tissue. Gene therapy directed to arterial wall cells, however, has limitations in the delivery to complicated arterial lesions and efficiency of gene transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficiency of gene transfer to the atherosclerotic vessel is an important issue, because low efficiency was reported in a rabbit's model of angioplasty [28]. Therefore, we examined the efficacy of gene transfer to the endothelium of atherosclerotic vessels using cholesterol-fed monkeys [29].…”
Section: Gene Transfer To Blood Vesselsmentioning
confidence: 99%
“…Other homeobox genes have been shown to function as regulators of cellular differentiation and growth, 7,8 we have shown that overexpression of the Gax gene in normal rat carotid and rabbit iliac arteries can inhibit the fibro-proliferative response to balloon injury, 20,21 an effect that may be mediated by its ability to suppress integrin expression. 22 Adenovirus-mediated gene transfer performed in atheromatous vessels [23][24][25][26][27] combined with stent implantation [28][29][30][31][32][33][34] constitute two important challenges for clinical application. Here, we present the results of percutaneous adenovirus-mediated Gax gene transfer to atheromatous, stented rabbit iliac arteries in a clinical model of balloon angioplasty performed with the channel balloon catheter.…”
Section: Introductionmentioning
confidence: 99%